2023
DOI: 10.1186/s13059-023-03026-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species oncogenomics offers insight into human muscle-invasive bladder cancer

Kim Wong,
Federico Abascal,
Latasha Ludwig
et al.

Abstract: Background In humans, muscle-invasive bladder cancer (MIBC) is highly aggressive and associated with a poor prognosis. With a high mutation load and large number of altered genes, strategies to delineate key driver events are necessary. Dogs and cats develop urothelial carcinoma (UC) with histological and clinical similarities to human MIBC. Cattle that graze on bracken fern also develop UC, associated with exposure to the carcinogen ptaquiloside. These species may represent relevant animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 113 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…In addition to cfDNA in the blood, cfDNA in the urine of dogs has also been used for genomic characterisation. For example, NGS of FFPE tissue samples has demonstrated the presence of the somatic BRAF p.V595E mutation in a significant proportion of canine urinary bladder urothelial carcinomas (UC) [ 24 ], while a study using NGS identified the presence of the tumour genotype ( BRAF p.V595E) in 9/9 of the matched urine sediment samples from dogs with urinary bladder UC [ 25 ]. Similarly, using PCR and Sanger sequencing (a technique detailed in Section 3.4 ), the results of BRAF p.V595E analysis in dogs with or without urinary bladder UC were identical between the FFPE tissue, cytological smear and urine sample [ 26 ].…”
Section: Methods For Sampling Tumour Cells In Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cfDNA in the blood, cfDNA in the urine of dogs has also been used for genomic characterisation. For example, NGS of FFPE tissue samples has demonstrated the presence of the somatic BRAF p.V595E mutation in a significant proportion of canine urinary bladder urothelial carcinomas (UC) [ 24 ], while a study using NGS identified the presence of the tumour genotype ( BRAF p.V595E) in 9/9 of the matched urine sediment samples from dogs with urinary bladder UC [ 25 ]. Similarly, using PCR and Sanger sequencing (a technique detailed in Section 3.4 ), the results of BRAF p.V595E analysis in dogs with or without urinary bladder UC were identical between the FFPE tissue, cytological smear and urine sample [ 26 ].…”
Section: Methods For Sampling Tumour Cells In Dogsmentioning
confidence: 99%
“…Other studies have used WES analysis to interrogate the genetics of canine tumours. For example, several groups have performed WES analyses of canine urinary bladder urothelial carcinomas (UCs) and identified BRAF as the most recurrently mutated gene, in particular, the hotpot V595E mutation, which was found in the majority of samples [ 24 , 82 ]. WES analysis of trio samples of canine primary OSA versus OSA metastasis versus normal tissue from the same dog ( n = 10) showed that 4/10 (40%) metastases showed the acquisition of a likely pathogenic driver mutation that was not present in the primary tumour [ 80 ].…”
Section: Methods For the Genetic Characterisation Of Tumour Cells In ...mentioning
confidence: 99%